Towards identifying the active sites on RuO2 (110) in catalyzing oxygen evolution - Rao,RM; Kolb,MJ; Halck,NB; Pedersen,AF; Mehta,A; You,H; Stoerzinger,KA; Feng,Z; Hansen,HA; Zhou,H; Giordano,L; Rossmeisl,J; et al. (Energy and Environmental Science, 2017)
While the surface atomic structure of RuO2 has been well studied in ultra high vacuum, much less is known about theinteraction between water and RuO2 in aqueous solution. In this work, in situ surface X-ray scattering measurementscombined with density functional theory (DFT) was used to determine the surface structural changes on single-crystalRuO2 (110) as a function of potential in acidic electrolyte. The redox peaks at 0.7, 1.1 and 1.4 V vs. reversible hydrogenelectrode (RHE) could be attributed to surface transitions associated with the successive deprotonation of -H2O on thecoordinatively unsaturated Ru sites (CUS) and hydrogen adsorbed to the bridging oxygen sites. At potentials relevant tothe oxygen evolution reaction (OER), an –OO species on the Ru CUS sites was detected, which was stabilized by aneighboring -OH group on the Ru CUS or bridge site. Combining potential-dependent surface structures with theirenergetics from DFT led to a new OER pathway, where the deprotonation of the -OH group used to stabilize –OO wasfound to be rate-limiting.